2016
DOI: 10.11114/jets.v4i11.1820
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Folk Dance Training on 5-6 Years Children’s Physical and Social Development

Abstract: The purpose of this study is to analyze the effects of folk dance training on 5 -6 year old Pre-school children"s physical and social development. The experimental design with an experimental and control group was used in accordance with the quantitative research methods in this research. The research has been conducted with the participation of 40 children. During the research, 32 hours of folk dance training instructed in all, across two months with 4 training periods in a week. Control group students were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 5 publications
0
22
0
1
Order By: Relevance
“…Other studies that were at the lower end of the distribution were Koch et al (2015a,b) that included an anti-violence training ( d = 0.02) and Ho et al (2016a) that aimed to improve the quality of life of cancer patients ( d = 0.06). On the other side of the distribution, we could observe large effect sizes ( d = 1.8 up to d = 2.96) in the studies of Cruz-Ferreira et al (2015), Biber (2016), Teixeira-Machado et al (2017), and Aithal and Karkou (2018). If we had not recoded the effect sizes from Chiang et al (2016), Pohlmann et al (2017), Teixeira-Machado et al (2017), and Aithal and Karkou (2018) at Level IV, they would have been even larger (up to d = 5.07).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Other studies that were at the lower end of the distribution were Koch et al (2015a,b) that included an anti-violence training ( d = 0.02) and Ho et al (2016a) that aimed to improve the quality of life of cancer patients ( d = 0.06). On the other side of the distribution, we could observe large effect sizes ( d = 1.8 up to d = 2.96) in the studies of Cruz-Ferreira et al (2015), Biber (2016), Teixeira-Machado et al (2017), and Aithal and Karkou (2018). If we had not recoded the effect sizes from Chiang et al (2016), Pohlmann et al (2017), Teixeira-Machado et al (2017), and Aithal and Karkou (2018) at Level IV, they would have been even larger (up to d = 5.07).…”
Section: Resultsmentioning
confidence: 69%
“…The inclusion of studies with baseline differences is justified here, because our methodological approach takes those differences into account when calculating effect sizes. The studies from Biber (2016), Guerra-Balic et al (2017), Meric and Ilhan (2016), and Panagiotopoulou (2018) used no statistical tests to assess baseline differences.…”
Section: Resultsmentioning
confidence: 99%
“…The above result was in agreement with the following studies conducted by proved that Korean traditional dance program improved the health-related fitness of Korean elderly females. Also, Biber (2016) proved that folk dance training significantly improved children"s physical fitness development. More ever (Vordos et al, 2017) revealed that traditional Greek dance significantly improves muscular strength and lower limb endurance.…”
Section: Discussionmentioning
confidence: 95%
“…Dance helps participants develop physical fitness and thus shares many of the health benefits of other sporting events (Nhamo & Magonde, 2013). Folk dance training can significantly improve the physical fitness level of per-Scholl children (Biber et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They also evolve spontaneously out of an inner need to express oneself. Many studies (Biber, 2016;Chronopoulou & Riga, 2012;Frid et al, 2016;Han et al, 2003;Howard-Jones et al, 2002;Kiehn, 2003Kiehn, , 2007MacDonald et al, 2006;Morin, 2001;Niland, 2009;Russ et al, 1999;Soley & Spelke, 2016;Sternberg, 2006;Tarnowski, 1999) prove that such a creative approach in children occurs automatically, and, in particular, highlight the positive influence on the common or individual improvisational motivation within the concept of flow in play. All these characteristics -together with improvisation and composition -are pursued by the Slovene curriculum for music education in primary school (Učni načrt za glasbeno vzgojo v osnovni šoli, 2011), which establishes educational objectives in the sense of holistic teaching and defines music as a "cultural phenomenon" (ib., p. 39) and as "an individual's need for an organised acoustic environment, sound-based communication and creativity" (ib.).…”
Section: Introductionmentioning
confidence: 99%